التّعدد اللّغوي والتّنوع الثّقافي في الجزائر بين اللّغات الرّسمية واللّهجات المحلية الممارسات اللّغوية لمنطقة بوسمغون أنموجا: Multilingualism and cultural diversity in Algeria between official languages and local dialects Language practices of Boussemghoun region as a model - لعمري محمد (Maalim, 2022)
This article aims to highlight the reality of multilingualism in Algeria, official languages, and colloquial dialects in light of the country's cultural diversity, as well as to investigate the implications and the efforts of effective linguistic planning to address the phenomenon. The study also dealt with how to adjust the phenomenon and make it an enrichment and integration factor by monitoring some language practices of Boussemghoun region citizens in the province of Bayadh as a model for studying linguistic, dialectic, and cultural diversities in linguistic practices and their relationship to population movements. This study reached several conclusions, most notably the coexistence of Modern Standard Arabic and Tamazight in a way that is integrated with local dialects in Algeria in general and the Boussemghoun region in particular. It also concluded that language practices of the People of Boussemghoun tolerated a combination of Arabic, Shilha, colloquial and French compositions in their linguistic performance.